2014
DOI: 10.1007/s12039-014-0605-0
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxylate as a reducing agent for manganese(III) in salen scaffold: A kinetics and mechanistic study

Abstract: The kinetics of oxidation of glyoxylic acid (HGl) by Mn III (salen)(OH 2) + 2 ((H 2 salen = N,Nbis(salicylidene)ethane-1,2-diamine) is investigated at 30.0-45.0 • C, 1.83 ≤ pH ≤ 6.10, I = 0.3 mol dm −3 (NaClO 4). The products are identified as formic acid, CO 2 and Mn II with the reaction stoichiometry, | [Mn III ]/ [HGl]| = 2. The overall reaction involves fast equilibrium pre-association of Mn III (salen)(OH 2) + 2 with HGl and its conjugate base Gl − forming the corresponding inner sphere complexes (both HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The mass spectrum was recorded on a Macromass Q-TOF ESI-MS mass spectrometer. 1 Figure S3a, Supplementary Information) as observed for this complex in CD 3 OD by Ciringh et al 8 The weak and broad imine proton resonance reported by Ciringh et al, (at −398 ppm) 8 lies far beyond the accessible range probed in the present work. The chemical shifts of Mn III Schiff base complexes have been attributed to the contact term which occurs through phenoxide oxygen and the imine group.…”
Section: Physical Measurementssupporting
confidence: 49%
See 3 more Smart Citations
“…The mass spectrum was recorded on a Macromass Q-TOF ESI-MS mass spectrometer. 1 Figure S3a, Supplementary Information) as observed for this complex in CD 3 OD by Ciringh et al 8 The weak and broad imine proton resonance reported by Ciringh et al, (at −398 ppm) 8 lies far beyond the accessible range probed in the present work. The chemical shifts of Mn III Schiff base complexes have been attributed to the contact term which occurs through phenoxide oxygen and the imine group.…”
Section: Physical Measurementssupporting
confidence: 49%
“…The stock solution of NaClO 4 was prepared and standardized as described earlier. 1 The stock solution of the complex (5 × 10 −3 mol dm −3 , pH 5, 10% v/v MeOH/water) was protected from light and stored in a refrigerator at ∼ 20 • C when not in use. It was not allowed to age for more than 24 h.…”
Section: 1a [Mnmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the studies devoted to understand the mechanisms of ligand substitution and redox reactions of Mn III are limited. In view of the importance of oxalate in biology and Mn III (salen) as a suitable oxidant for oxalate oxidation, we, in continuation of our other investigations 16,17 of the mechanism of ligand substitution and electron transfer at the Mn III centre, present here a thorough study on trans-Mn III (salen)(OH 2 ) 2 + + oxalate system over extended pH and temperature ranges. To the best of our knowledge there is no earlier literature report on such a study, although oxidation of oxalate by higher valent manganese has been the topic of several investigations in the past.…”
Section: Introductionmentioning
confidence: 90%